Critical Discourse Analysis Model Teun A. van Dijk in the Lyrics of the Song 'Cabe-Cabean' by Tjahjadi/Ishak as a Medium for Social Education - Budi, Imanuel Setyo; Suandi, I Nengah; Sudiana, I Nyoman; Dewantara , I Putu Mas (Journal of Practice Learning and Educational Development, 2025)
This article aims to conduct a critical discourse analysis using Teun A. van Dijk's model to examine the lyrics of the song "Cabe-Cabean" by Tjahjadi/Ishak.This analysis reveals how power, ideology, and social structure are contained within the discourse of the song, particularly in relation to gender, materialism, and social norms.This article focuses on the four main components in van Dijk's model, namely social structure, cognitive structure, text structure, and communicative context.By analyzing the song lyrics, this research shows how the song reinforces negative stereotypes about women, depicting them as materialistic and unserious in social relationships.The analysis results show that although this song is entertaining, it subtly reinforces negative ideologies and encourages listeners to be more critical in consuming media.This research contributes to understanding how popular music can serve as a means of disseminating cultural ideology and shaping public perception in contemporary society.